APPLICATION OF BOKASHI SLUDGE BIOGAS FERTILIZER IN LAMTORO LEAVES AT THE EARLY GROWTH OF LAMTORO TARRAMBA WITH DIFFERENT LEVELS - Arwati Ata Linda; I Made Adi Sudarma (Bajang Institute, 2023)
This study aims to determine the application of bokashi sludge biogas fertilizer from lamtoro leaves on the early growth of Tarramba lamtoro with different levels. This study used a completely randomized design (CRD) with 5 treatments and 4 replications. The treatments tested were without fertilizer/polybag (P0), 200 gram/polybag (P1), 400 gram/polybag (P2), 600 gram/polybag (P3) fertilizer, and 800 gram/polybag (P4). The variables measured in this study were plant height, number of compound leaves (strands), stem diameter, and petiole. The results of this study showed that there was a significant effect (P<0.05) on the growth of the 6th week except for the number of compound leaves. Lamtoro Tarramba plant growth with bokashi sludge biogas fertilizer from lamtoro leaves at the best level of treatment P4(800) gram/polybag at week 6 where the plant height was 48.33 cm, stem diameter was 3.63 cm, number of compound leaves 95.33 leaves. It was concluded that the application of lamtoro leaf biogas sludge with level 800 grams to the lamtoro Tarramba plant give the best result.